Three-dimensional discrete element modeling of direct shear test for granular rubber–sand. (May 2018) - Wang, Can; Deng, An; Taheri, Abbas
Abstract: Three-dimensional discrete element modeling of direct shear test conducted on granular rubber–sand is presented. Excellent agreement was attained between the simulation and test results, verifying the model's capacity of examining mixtures shear behavior. Important particulate-scale observations were attained, including the inter-particle contacts force, particles displacement and rotation, porosity and their variation with rubber particle contents. The observations demonstrate that the rubber particles inclusion amends the mixture stiffness, grading and packing at the particulate level, leading to a corresponding variation in the material shear behavior. Some interesting particulate-level simulations were examined to gain further insight into micro-mechanic characteristics of the mixtures.